2011
DOI: 10.1037/a0022642
|View full text |Cite
|
Sign up to set email alerts
|

On the nature of identity fusion: Insights into the construct and a new measure.

Abstract: Previous research has documented the consequences of feeling fused with a group; here we examine the nature of identity fusion. Specifically, we sought to determine what fusion is and the mediating mechanisms that lead fused individuals to make extraordinary sacrifices for their group. Guided by the assumption that fusion emphasizes the extent to which people develop relational ties to the group, we developed a measure designed to capture feelings of connectedness and reciprocal strength with the group. In 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
480
4
65

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 343 publications
(569 citation statements)
references
References 59 publications
20
480
4
65
Order By: Relevance
“…Fusion with the Tamborrada group was measured using the 7-item verbal fusion scale (e.g., "I am one with my group") (Gómez et al, 2011). Respondents indicated the degree to which each statement reflected their relationship with their Tamborrada group on scales ranging from 0 (strongly disagree) to 6 (strongly agree).…”
Section: Pre-event (T1) and Post-event (T3) Measuresmentioning
confidence: 99%
“…Fusion with the Tamborrada group was measured using the 7-item verbal fusion scale (e.g., "I am one with my group") (Gómez et al, 2011). Respondents indicated the degree to which each statement reflected their relationship with their Tamborrada group on scales ranging from 0 (strongly disagree) to 6 (strongly agree).…”
Section: Pre-event (T1) and Post-event (T3) Measuresmentioning
confidence: 99%
“…Second, activating a high identifiers self-views should also activate pro-relationship behaviour. Research by Gómez et al (2011) on identity fusion, the extent to which individuals' self-identities becomes fused with their group identities, has shown that when the self-views of highly fused participants are challenged, they are more likely to endorse extreme group behaviour. They argued that because challenging the personal self-views of fused persons resulted in similar outcomes as when their group identities were challenged, their personal and group identities were functionally equivalent.…”
Section: Self-views and Relationship-specific Identificationmentioning
confidence: 99%
“…That is, the personal identity of fused people is functionally equivalent to their groups' identities (Swann et al, 2009). Strong association between fusion and radical attitudes has been confirmed (Gómez et al, 2011), as has the role of self-verification strivings: fused individuals were especially prone to express radical pro-group opinions and fight on behalf of their fellow group members when their self-schema has been challenged (Swann et al, 2009). Furthermore, an elevated feeling of agency (i.e., by physical activities) results in the endorsement of pro-group activities among fused persons (Swann et al, 2010b).…”
Section: Overviewmentioning
confidence: 84%
“…The only differences were adding a locus of control scale and a social desirability scale. Both scales are tested and validated in the Poland Delta Questionnaire (Drwal, 1995). This questionnaire consists of 24 "true-false" items, out of which 14 constitute the locus of control scale (LOC, e.g., "Very often I feel I have no influence over what happens to me", "Getting a good job mostly depends on a lucky coincidence", etc.…”
Section: Methodsmentioning
confidence: 99%